Efek Hepatoprotektif Ekstrak Etanol Brokoli (Brassica oleracea L. var. italica) terhadap Kerusakan Histologis Sel Hati Tikus Wistar yang Diinduksi DMBA (Hepatoprotective Effect of Ethanolic Extract of Broccoli (Brassica oleracea L. var. italica) on the Histologically Damage of Wistar Rats Liver Cell Induced by DMBA) - Muhtar Ady Kusuma; Elly Nurus Sakinah; Rosita Dewi (Pustaka Kesehatan, 2017)
DMBA (7,12-Dimethylbenz(α)antracene) is one of Polycyclic Aromatic Hydrocarbon’s form that is abundant on air pollution, i.e. automobile exhaust, cigarette smoke, and wood stoves. DMBA is metabolized in liver result in DMBA-DE. DMBA-DE is a free radical compound that has hepatotoxic effect. Broccoli contains flavonoid that has antioxidant effect. It can stabilize DMBA-DE radical compound. This research was conducted to investigate the hepatoprotective effect of ethanolic extract of broccoli on the damage of rat’s liver cells induced by DMBA. This research used 30 white male rats that was divided into 6 groups: normal control (aquadest), positive control (DMBA) and the treatment groups(using brocolli ethanolic extract with dose : 250, 500, 1000, and 2000 mg/kgBB). The treatment was given for 7 days followed by single-dose DMBA 15 mg/kgBB induction in the 8th day. Histological appearance of liver cells were examined on the 12th day. Data were analyzed by using Kruskal Wallis test followed by Mann Whitney. The result showed that there was a significant difference among the groups with p<0.05. In conclusion, there were some differences of hepatoprotective effect of broccoli ethanolic extract on the histologically damage of rats liver cells induced by DMBA. Keywords: ethanolic extract of broccoli, DMBA, histopathology, hepatoprotective